Provocation to a Final Resistance of Truth: Ethics of a Heretical Discourse - Sadiku, Artan (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Artan Sadiku Title (English): Provocation to a Final Resistance of Truth: Ethics of a Heretical Discourse Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011) Publisher: Department of Gender Studies, Euro-Balkan Institute Page Range: 69-80 Page Count: 11 Citation (English): Artan Sadiku, “Provocation to a Final Resistance of Truth: Ethics of a Heretical Discourse,” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011): 69-80.